2020
DOI: 10.48550/arxiv.2006.14636
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stellar Masses of Giant Clumps in CANDELS and Simulated Galaxies Using Machine Learning

M. Huertas-Company,
Y. Guo,
O. Ginzburg
et al.

Abstract: A significant fraction of high redshift star-forming disc galaxies are known to host giant clumps, whose formation, nature and role in galaxy evolution are yet to be understood. In this work we first present a new automated method based on deep neural networks to detect clumps in galaxy images and show that it is more sensitive and faster than previous proposed methods. We then use this method to systematically detect clumps in the rest-frame optical and UV images of a complete sample of ∼ 1500 star forming ga… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 81 publications
1
10
1
Order By: Relevance
“…Lower clumpy fractions are found in galaxies that have low sSFRs compared to the main sequence, with the clumpy fractions increasing by ∼10% at the highest ∆ log(sSFR) bin. This is different what was reported by Huertas-Company et al (2020), where they observed lower clumpy fractions that show no dependencies on ∆ log(sSFR).…”
Section: Dependency Of Clumps On Ssfrscontrasting
confidence: 99%
See 2 more Smart Citations
“…Lower clumpy fractions are found in galaxies that have low sSFRs compared to the main sequence, with the clumpy fractions increasing by ∼10% at the highest ∆ log(sSFR) bin. This is different what was reported by Huertas-Company et al (2020), where they observed lower clumpy fractions that show no dependencies on ∆ log(sSFR).…”
Section: Dependency Of Clumps On Ssfrscontrasting
confidence: 99%
“…The methodologies for detecting clumps vary from studies to studies, and no universal way have been defined. A number of methods have been used to detect clumpy structures, but the majority are based on identifying pixels with enhanced intensity through a computer algorithm (e.g., Wuyts et al 2012;Guo et al 2015;Zanella et al 2019;Huertas-Company et al 2020). Our normalized profiles naturally allow us to perform a similar analysis.…”
Section: Classification Scheme For Clumpy Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The method of skip links provides the machine additional information on how to reconstruct the image. The UNet has already been used in other astrophysical studies (Hausen & Robertson 2020;Huertas-Company et al 2020;Hong et al 2020;Boucaud et al 2020).…”
Section: Unet -Detectionmentioning
confidence: 99%
“…The images of high-redshift discs typically show giant clumps. The clumps are especially pronounced in rest-frame UV and H 𝛼 emission maps, which serve as star-formation tracers (Elmegreen & Elmegreen 2006;Genzel et al 2006Genzel et al , 2008Förster Schreiber et al 2009Wuyts et al 2012Wuyts et al , 2013Guo et al 2015;Shibuya et al 2016;Guo et al 2018;Huertas-Company et al 2020). Clumps are also detected in interferometric submilimeter observations.…”
Section: Introductionmentioning
confidence: 95%